International assistance to democratic reform in Ukraine: an opportunity missed or an opportunity squandered?. Issue 6 (19th September 2017) - Leitch, Duncan
ABSTRACT: The article examines the impact of international expert advice on efforts to introduce democratizing reforms in Ukraine's system of public administration following independence in 1991. The focus of the analysis is on an area which has particular resonance in the light of recent events in Ukraine, the relationship between Kyiv and the regions. The article argues that the effectiveness of external assistance has been compromised as much by institutional factors affecting the behaviour of international donors as by corresponding factors on the Ukrainian side, and that an opportunity to contribute to the democratic transformation of Ukraine has been needlessly wasted.